Self-breast examination: knowledge, attitude and practice of Nigerian university students (2016)
Introduction: Breast cancer is one of the major cancers with high mortality rate both globally and locally and is one of the commonest cancers in Nigeria. Self-breast examination is one of the ways of identifying breast lumps among adolescents and young adult. There is need to ascertain that self-breast examination (SBE) is properly practice among the young women in Nigeria as a means of early detection and curative treatment. This behaviour could curtail the late stage presentation and poor prognosis of this disease. Objectives: The objective of this study therefore was to establish the knowledge, attitude and practice of self-breast examination among the undergraduate students of the University of Ibadan. Method: This is a survey research design. Two hundred and twenty eight students (228) were selected by stratified random and purposive sampling of three faculties of the University. A validated questionnaire called Female Self-Breast Examination (FBSE) inventory was used to collect data for the study. Data collected was analyzed descriptively. Result: The age range of the students was between 18-32 years. One hundred and ninety five (85.5%) of the students knew about cancers and 225 (98.7%) have heard about breast cancer. One hundred and forty eight (64.9%) heard of breast cancer from television and 188 (82.5%) have heard about self-breast examination. One hundred and twenty two (53.2%) of the students knew what self-breast examination is used for while 106 (46.8%) did not. Eleven (4.8%) practice self-breast examination regularly while one hundred and seventy one (75%) of the students will like to be taught how to do self-breast examination. Neither age nor course/area of study has influence either on the knowledge or practice of the students concerning breast examination. Knowledge of breast cancer and self-breast examination are correlated with good attitudes towards SBE (r = 0.196; p <0.01). Similarly attitudes of the Nigerian University students towards self-breast were better in some faculties than the others; notably medicine > social science > education (r= 0.147; p<0.05). Conclusion: Information, Education and Communication (IEC) in regard of breast' cancer and SBE activities should be given to all Nigerian secondary and tertiary institutions and other developing and resource-poor countries.